(untitled) (Journal of Finance, Business and Management Studies, 2021)
The study is to estimate the endogenous variables of monetary policy to understand the response and interaction among the variables. I use the linearized DSGE model, and the findings suggest that the monetary policy shock leads inflation falls and interest rate rises but change in interest rate decreases output.